Effect of the Incorporation of Bactericidal Agents Ag, Cu, and Zn Through Micro-arc Oxidation on the Properties of the Ti-25Ta Alloy Surface - Kuroda, Pedro Akira Bazaglia; Cardoso, Giovana Collombaro [UNESP]; Rossi, Mariana Correa; Grandini, Carlos Roberto [UNESP]; Afonso, Conrado Ramos Moreira (FapUNIFESP (SciELO), 2024)
The main objective of this paper is to produce an anodic layer of TiO2 rich in calcium, phosphorus, and magnesium using the anodizing technique known as micro-arc oxidation (MAO) on the Ti-25Ta alloy together with the incorporation of silver (Ag), copper (Cu) and zinc (Zn) metallic ions using different electrolytes. The structural changes and microstructures on the MAO surfaces were analyzed using the X-ray diffraction (XRD) technique and scanning electron microscopy (SEM). The chemical composition to verify whether silver, copper, and zinc were incorporated via energy dispersive spectroscopy (EDS) and surface characteristics such as wettability and hardness of the coatings were also investigated. From the EDS mapping results, it is observed that the MAO process was effective in incorporating the ions present in the electrolyte. Regarding X-ray diffraction patterns, the TiO2 phases formed in the Ti-25Ta alloy has a mixture of anatase and rutile, making the MAO surface hydrophilic. The Ag element surface is thicker than the films containing Cu and Zn, as the Ag ions have high electrical conductivity, accelerating the oxidation process during surface treatment. Regarding hardness, coating containing Cu have a higher hardness value.
Keywords: Bactericidal agents; biomaterial; ion incorporation; surface modification; Ti alloy